Improving the Reliability Performance for Radar System Based on Rayleigh Distribution - Adel A. El-Faheem; Abdelfattah Mustafa; Tasnem Abd El-Hafeez (Scientific African, 2022)
The reliability equivalence factors are obtained for a Radar system. Radar system consists of three components, with Rayleigh distribution with two parameters. Rayleigh distribution has non-constant failure rate. This system is improved using two main methods: reduction and redundancy methods. The mean time to failure and gamma fractiles are derived to compare the improved methods. A numerical study is discussed.